State of viral hepatitis knowledge and testing uptake in Brazil: Findings from the National Survey of Knowledge, Attitudes and Practices (PCAP-2013). Issue 1 (December 2016) - de Oliveira, Silvano; Sabidó, Meritxell; Pascom, Ana; Gisiviez, Juliana; Benzaken, Adele; Mesquita, Fábio
Abstract Background Data were obtained from the third National Survey of Knowledge, Attitudes and Practices of HIV and other Sexually Transmitted Infections (STI) (PCAP-2013) and used to describe the current state of viral hepatitis (VH) knowledge and screening as well as the prevalence of viral hepatitis B (HBV) vaccination in Brazil and to assess the factors associated with testing uptake. Methods A probability sample survey of 12, 000 individuals (50 % men) aged between 15 and 64 years was conducted between October and December of 2013. The participants completed the survey in their own homes through computer-assisted face-to-face interviews and self-interviews. We analysed data related to self-reported knowledge of VH routes and screening uptake after weighting the variables to account for unequal selection probabilities and correct for differences in sex, age and region according to 2010 census figures. Results The levels of correct knowledge regarding HBV and HCV transmission through unprotected sex were 33.1 and 34.3 %, respectively. The levels of correct knowledge regarding HBV and HCV transmission through tattooing/piercing were 26.4 and 24.5 %, respectively. Overall, 29 % of the respondents reported having underwent VH screening and 73.9 % reported prior HBV vaccination. VH screening was associated with the following factors: age between 25 and 49 years (adjusted male odds ratio (OR): 2.29, [95 % confidence interval (CI): 1.83–2.87]; female OR: 1.36, [95 % CI: 1.10-1.67]); age between 50 and 64 years (male OR: 1.52, [CI: 1.13–2.03]; female OR: 1.29, [CI: 1.02–1.63]); initial sexual intercourse before the age of 15 years in men (OR: 1.32, [CI: 1.10–1.57]); higher socioeconomic statuses of group A (male OR: 2.38, [CI: 1.81–3.13]; female OR: 2.10, [CI: 1.66–2.68]) and B (female OR: 1.56, [CI: 1.27–1.93]); and having ever been tested for HIV (male OR: 7.50, [CI: 5.82–8.53]; female OR: 7.13, [CI: 5.97–8.54]). Conclusions This study revealed low levels of knowledge regarding VH transmission and screening practices in the general Brazilian population, especially among younger individuals and those with lower socioeconomic status. Efforts to enhance awareness campaigns and expand testing sites are needed to remove barriers to testing.